2015
DOI: 10.1016/j.bone.2015.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Androgen receptors and experimental bone loss — an in vivo and in vitro study

Abstract: Testosterone is a sex hormone that exhibits many functions beyond reproduction; one such function is the regulation of bone metabolism. The role played by androgen receptors during testosterone-mediated biological processes associated with bone metabolism is largely unknown. This study aims to use a periodontal disease model in vivo in order to assess the involvement of androgen receptors on microbial-induced inflammation and alveolar bone resorption in experimental bone loss. The impact of hormone deprivation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 59 publications
(79 reference statements)
1
34
2
1
Order By: Relevance
“…Due to the conversion of testosterone in estradiol, we used a pharmacologic model of androgen receptor blockade (administering flutamide) to compare the results with the orchiectomy model, thus isolating the impact of androgens on bone, obtaining similar clinical results. In vitro , we demonstrated that physiologic testosterone levels (10 nM), but not low or high levels, are able to downregulate osteoclastogenesis both directly and indirectly, decreasing murine osteoblasts‐derived RANKL expression . Using data from the III National Health and Nutrition Examination Survey, we showed a positive association between high total TES and bioavailable testosterone and the presence and severity of periodontitis …”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…Due to the conversion of testosterone in estradiol, we used a pharmacologic model of androgen receptor blockade (administering flutamide) to compare the results with the orchiectomy model, thus isolating the impact of androgens on bone, obtaining similar clinical results. In vitro , we demonstrated that physiologic testosterone levels (10 nM), but not low or high levels, are able to downregulate osteoclastogenesis both directly and indirectly, decreasing murine osteoblasts‐derived RANKL expression . Using data from the III National Health and Nutrition Examination Survey, we showed a positive association between high total TES and bioavailable testosterone and the presence and severity of periodontitis …”
Section: Discussionmentioning
confidence: 88%
“…Low testosterone levels have been extensively related with a number of clinical alterations of normality, including libido and sexual function loss, muscular strength loss, fatigue, cognitive and mood alterations, as well as an increase in cardiovascular disease markers, mortality, diabetes mellitus, metabolic syndrome and increased risk for bone fracture . Our group has demonstrated that not only low levels of testosterone, as those obtained after orchiectomy, increase ligature‐induced periodontal bone loss in rats, but also supraphysiologic levels of the hormone . Due to the conversion of testosterone in estradiol, we used a pharmacologic model of androgen receptor blockade (administering flutamide) to compare the results with the orchiectomy model, thus isolating the impact of androgens on bone, obtaining similar clinical results.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our research group has shown the complexity of biological responses associated with both decrease and increase of testosterone levels in the experimental periodontal disease model . Short‐term reduction of testosterone levels in young animals caused an increase of inflammatory bone resorption and osteoclast numbers with a corresponding increase in locally‐produced IL‐1β in vivo; whereas in vitro testosterone suppressed RANKL‐induced osteoclastogenesis .…”
Section: Introductionmentioning
confidence: 99%